Pharmacokinetics of flavanone glycosides after ingestion of single doses of fresh-squeezed orange juice versus commercially processed orange juice in healthy humans - Silveira, Jacqueline Queiroz da [UNESP]; Cesar, Thais Borges [UNESP]; Manthey, John A.; Baldwin, Elizabeth A.; Bai, Jinhe; Raithore, Smita (Amer Chemical Soc, 2014)
Orange juice is a rich source of flavonoids considered beneficial to cardiovascular health in humans. The objective of this study was to analyze the pharmacokinetics of the main flavanone glycosides, hesperidin and narirutin, in humans after the consumption of two styles of orange juice, fresh-squeezed (FOJ) and commercially processed (POJ), differing in their amounts of soluble and insoluble forms of these compounds. Healthy human subjects consumed 11.5 mL/kg body weight of FOJ, and after an interval of 30 days, consumed the same quantity of POJ. The results showed that there were no significant differences in the Tmax of the pharmacokinetic curves for the metabolites of hesperidin and narirutin following the consumption of the two styles of juices, and corrected for differences in doses in the POJ and FOJ, there were also no significant differences in the AUC and Cmax values and percent absorption of these compounds.
Keywords: Bioavailability; Pharmacokinetics; Hesperidin; Narirutin; Metabolites; Juice cloud